Respuesta :

it is negative two.

do what is in the () first. 

(-4+4)= 0

multiply

-6*0= 0

4+or-0 = 4

-8/4

is 

-2

kanest
Since the denominator is an equation, we will have to solve it first before we can evaluate the fraction.

Use the order of operations to figure out what to work on first in the equation.

6(-4+4) involves parentheses, so solve this expression first.

[tex]-4 + 4 = 0[/tex]
[tex]6 * 0 = 0[/tex]

The equation will now become this:

[tex]4 - 0 = 4[/tex]

The denominator in this fraction is now 4. Your fraction should now be this:

[tex]- \frac{8}{4} [/tex]

The negative sign is applied to the entire fraction.

Simplify the fraction.

[tex]- \frac{8}{4} = -2[/tex]

The expression is equal to -2.